Analisis Pengaruh Model Laba dan Model Arus Kas dalam Memprediksi Kondisi Financial Distress - Budi Harto; Lilis Saidah Napisah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This study aims to determine the effect of the profit and cash flow models in predicting financial distress conditions in the transportation company 2015-2018 period. The metode used is descriptive and verification method. The sampling was taken based on a purposive sampling method on mining sector companies listed on the IDX. The results showed that the profit proxied by Return on Assets (ROA) had a significant and significant effect on financial distress which was tested with the modified Altman Z-Score formula, and cash flow procied by Operating Cash Flow Ratio (OCFR) had a significant and significant effect on financial distress which was tested with the modified Altman Z-Score formula. While the results of the study indicate that profit and cash flow together have a significant effect on financial distress with the correlation coefficient showing a very strong relationship. Profit and cash flow influance financial distress of 68,3% and the remaining 31,7% is influenced by other factors.